The image of childhood in Susan Hill´s prose - Zemanová, Tereza (Univerzita Pardubice, 2009)
This paper focuses on depiction Susan Hill's concept of childhood. The main analytical part based on the selected prose by Hill featuring children and childhood aims to portray the image of childhood from the perspective of this authoress. The parallel themes of Hill's works addressing the family relationships, children fears and frustrations or evil in children are employed to find the characteristic features of Hill's view of childhood. Besides the major analysis of Hill's works a comparison with other writers illustrating childhood is provided.
Keywords: Susan Hill; Children; childhood; children frustrations; evil in children; families; Susan Hillová; Děti; dětství; dětské frustrace; zlo v dětech; rodiny